Principles of Language Politeness in Najwa's Eyes in Trans 7 - Mulia Agustina; Jamilin Tinambunan; Sri Rahayu (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This research is motivated by a violation of the principle of politeness in language, because the event is more dominant with questions. The problem studied in this study is how are the maxims of wisdom, generosity, appreciation, simplicity, consensus and sympathy in the principles of language politeness in the speech of the presenters and guest stars in the Mata Najwa program on Trans 7? This study aims to describe, analyze, and interpret "Principles of Language Politeness in Mata Najwa in Trans 7". The theory used in this study is the theory of Chaer (2010) and Leech (1993). The method used in this research is descriptive method. The research approach that the author uses is qualitative research. Data collection techniques used in this study are observation, documentation, listening and note-taking techniques. The results of the author's research can be concluded that the principle of politeness in the eyes of Najwa in Trans7 uses a lot of polite language such as 1) the maxim of wisdom in the Mata Najwa event on Trans 7 shows the existence of speech that maximizes the benefits of others, 2) the maxim of generosity in the Mata Najwa event in Trans 7 shows an utterance that minimizes self-benefit, 3) The maxim of appreciation in the Mata Najwa event in Trans 7 shows an utterance that maximizes praise to others. 4) the maxim of simplicity in the Mata Najwa program on Trans 7 shows that there is an utterance that minimizes self-praise. 5) the maxim of consensus in the Mata Najwa event on Trans 7 shows the existence of speech that maximizes agreement with others., 6) the maxim of sympathy in the Mata Najwa event on Trans 7 shows the existence of speech that maximizes sympathy for others.